One-Pot Fabrication of Poly (Ionic Liquid)/TiO2 Composite as an Electrorheological Material With Enhanced Electro-Responsive Properties and Broader Operation Temperature Range - Zhang, Guangchen; Yang, Shu; Zhao, Zhenjie; Dong, Chenjie; Jin, Xiao; Wang, Li-Min; Liu, Ying Dan (Frontiers in Materials, 2022)
Poly(ionic liquid)/TiO2 composite particles were fabricated using a facile one-pot synthesis method, in which process the polymerization of ionic liquid monomer and the hydrolysis of precursor for TiO2 proceeded in one system. The morphological properties of the composite particles were observed by a scanning electron microscope and a transmission electron microscope. Chemical and physical structures of the particles were analyzed by a Fourier infrared spectrometer and an X-ray diffractometer respectively. It was found that in the composite particles, poly(ionic liquid) (PIL) spheres are embedded in the continuous TiO2 phase, forming larger nonspherical particles of ~ 10 microns. Rheological properties of PIL and the PIL/TiO2 composite particles dispersed in silicone oil were measured by a rotational rheometer with a high-power supply. The PIL/TiO2 particles showed higher shear stress and elastic modulus than that of pure PIL particles at the same electric field. In addition, comparing with pure PIL particles, the PIL/TiO2 particles are also able to work at higher temperature up to 100 ℃.